Understanding Patient Registries for Diabetes: A Scoping Review of Published Literature - Lana Moayad MD(C); Paige Alliston RD, MHSc; Saira Khalid BScN; Donna Fitzpatrick-Lewis MSW; Hertzel C. Gerstein MD, MSc; Diana Sherifali RN, PhD (Journal of Patient Experience)
Background: Diabetes registries have grown in prevalence and incorporated patient engagement opportunities to support diabetes management. We aimed to understand the goals, purpose, and context for diabetes registries defined as patient-focused and how people with diabetes are engaging with these registries. Methods: We searched Pubmed, MEDLINE, Embase, and Emcare using the following criteria: (1) the population is people with diabetes mellitus, including type 1, type 2, and/or gestational diabetes; and (2) the study describes a patient focused registry. Results: The search identified 346 citations, 9 of which were included. The goals of the registries included: developing referral systems, evaluating community-based interventions, collecting self-reported data, improving access to care, and fostering diabetes communities. The delivery settings were community-based, outpatient, or primary care. The methods of delivery and level of patient engagement varied between registries. Conclusions: This scoping review identified 9 diabetes registries, with varying goals, purposes and levels of patient engagement. It highlights a need for registries centered on people with diabetes to promote engagement and facilitate long-term diabetes self-management.